The culture of AI everyday life and the digital revolution - Elliott, Anthony 1964- (Routledge, 2019)
In this ground-breaking book, Cambridge-trained sociologist Anthony Elliott argues that much of what passes for conventional wisdom about artificial intelligence is either ill-considered or plain wrong. The reason? The AI revolution is not so much about cyborgs and super-robots in the future, but rather massive changes in the here-and-now of everyday life. In The Culture of AI, Elliott explores how intelligent machines, advanced robotics, accelerating automation, big data and the Internet of Everything impact upon day-to-day life and contemporary societies. With remarkable clarity and insight, Elliott's examination of the reordering of everyday life highlights the centrality of AI to everything we do - from receiving Amazon recommendations to requesting Uber, and from getting information from virtual personal assistants to talking with chatbots. The rise of intelligent machines transforms the global economy and threatens jobs, but equally there are other major challenges to contemporary societies - although these challenges are unfolding in complex and uneven ways across the globe. The Culture of AI explores technological innovations from industrial robots to softbots, and from self-driving cars to military drones - and along the way provides detailed treatments of: The history of AI and the advent of the digital universe; automated technology, jobs and employment; the self and private life in times of accelerating machine intelligence; AI and new forms of social interaction; automated vehicles and new warfare; and, the future of AI. Written by one of the world's foremost social theorists, The Culture of AI is a major contribution to the field and a provocative reflection on one of the most urgent issues of our time. It will be essential reading to those working in a wide variety of disciplines including sociology, science and technology studies, politics, and cultural studies